A Multidisciplinary Phenotyping and Genotyping Analysis of a Mapping Population Enables Quality to Be Combined with Yield in Rice - Calingacion, Mariafe; Mumm, Roland; Tan, Kevin; Quiatchon-Baeza, Lenie; Concepcion, Jeanaflor C. T.; Hageman, Jos A.; Prakash, Sangeeta; Fitzgerald, Melissa; Hall, Robert D. (Frontiers in Molecular Biosciences, 2017)
In this study a mapping population (F8) of ca 200 progeny from a cross between the commercial rice varieties Apo and IR64 has been both to genotyped and phenotyped. A genotype-by-sequencing approach was first used to identify 2681 polymorphic SNP markers which gave dense coverage of the genome with a good distribution across all 12 chromosomes. The coefficient of parentage was also low, at 0.13, confirming that the parents are genetically distant from each other. The progeny, together with both parents, were grown under irrigated and water restricted conditions in a random block design. All grain was harvested to determine variation in yield across the population. The grains were then polished following standard procedures prior to performing the phenotyping analyses. A Gas Chromatography - Mass Spectrometry approach was used to determine the volatile biochemical profiles of each line and after data curation and processing, discriminatory metabolites were putatively identified based on in-house and commercial spectral libraries. These data were used to predict the potential role of these metabolites in determining differences in aroma between genotypes. A number of QTLs for yield and for individual metabolites have been identified. Following these combined multi-disciplinary analyses it proved possible to identify a number of lines which appeared to combine the favourable aroma attributes of IR64 with the favourable (higher) yield potential of Apo. As such, these lines are excellent candidates to assess further as potential genotypes to work up into a new variety of rice which has both good yield and good quality, thus meeting the needs of both farmer and consumer alike.